2020
DOI: 10.2110/jsr.2020.48
|View full text |Cite
|
Sign up to set email alerts
|

Continental-slope instability triggered by seepage: An experimental approach

Abstract: Mass-transport complexes (MTCs), mass-transport deposits (MTDs), and associated facies and features are widely recognized in continental slopes around the world. In most current stratigraphic models of MTCs and MTDs, these submarine sediment failures are related to aquifer outflow (sapping, seepage) along continental slope fronts that originated during relative sea-level fall. We test a hypothetical scenario that is favored during early forced regression using reduced-scale physical simulation. A major undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…The present study extended the subaqueous slope experiments of Boffo et al . (2020) to investigate the effect of spring sapping from a confined aquifer in a partially subaqueous slope environment. Boffo et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study extended the subaqueous slope experiments of Boffo et al . (2020) to investigate the effect of spring sapping from a confined aquifer in a partially subaqueous slope environment. Boffo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Boffo et al . (2020) found that slope angle is an important parameter in the initiation of slope instabilities and mass flows by sapping. Lower aquifer discharge produced mass flows on steeper slopes, whereas the gentle slopes were more stable and needed higher aquifer discharges to produce slope instabilities and initiate mass flows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods such as physical model experiments [17][18][19][20][21], seepage experiments [22,23], numerical simulations [24][25][26][27][28], neural networks [29,30], and Bayesian networks [31] have all been employed in the study of slopes and foundation pits. However, most previous studies conducted separate tests, simulations, and analyses for a single problem.…”
Section: Introductionmentioning
confidence: 99%